The analysis of color choice peculiarities according to the liusher’s test among the emigrants and re-emigrants with depressive disorders - Венгер, Олена Петрівна (ScienceRise: Medical Science, 2016)
Aim of research – the study of characterological features of emigrants and re-emigrants by the analysis of color choices according to Lusher’s test. Methods. Examination was carried out using the method of colored choices (modified eight-color test of М. Lusher). Statistical analysis of the results was carried out using the distinct Fisher criterion. Results. We examined 196 emigrants, 191 re-emigrants and 198 persons that were not emigrants. The new data as to the influence of emigration and re-emigration factor on characterological features of patients with depressive disorders of psychogenic, endogenous and organic character are given in the work. There was demonstrated the formation of pathocharacterological features by hypothymic (dysthymic) type with the predomination of anxious-depressive features in emigrants and astheno-depressive ones in re-emigrants with the most expressed differences in the group of psychogenic depressions and the least expressed ones – in the group of depressive disorders. Conclusions. The results of research allow talk about the presence of pathocharacterological features by hypothymic (dysthymic) type in studied patients that must be considered within the main syndrome – depressive or anxious-depressive one in the context of influence of socio-psychological factors on the peculiarities of personal transformations. Emigration as a whole must be considered as the factor that favors pathocharacterological development in direction of the anxious-depressive changes and re-emigration – as the factor of astheno-depressive and apatho-depressive personal transformations. The influence of emigration and re-emigration factor on the personal features is mostly manifested in the group of psychogenic depressions and it is the least the group of organic depressive disorders